Prevalence and predictors of persistent cognitive and psychological symptoms in non-hospitalized post-COVID-19 patients seeking care at an outpatient post-COVID-19 clinic - Claessens, Gisela; Gerritzen, Iris; van Osch, Frits; van den Bergh, Joop P.; Verberne, Daan; Gach, Debbie; van Balen, Eric; van Heugten, Caroline M. (Frontiers in Psychology, 2024)
There is still much uncertainty about why some people develop persistent cognitive and mental health problems after SARS-CoV-2 infection and require additional care while others do not. In this study, we investigated the cognitive and psychological outcomes of non-hospitalized post-COVID-19 patients referred to an outpatient post-COVID-19 clinic for persistent symptoms more than 3 months after infection. Additionally, we aimed to explore the influence of demographic, physical, and personal factors on these outcomes.: This cross-sectional study was conducted at an outpatient post-COVID-19 clinic located at a prominent clinical teaching hospital in the Netherlands. Participants included non-hospitalized patients referred between 2020 and 2022, more than 3 months after SARS-CoV-2 infection, experiencing persistent symptoms. Main outcome measures included levels of anxiety and depression (Hospital Anxiety and Depression Scale), post-traumatic stress symptoms (PTSS) (Post-traumatic Stress Symptoms Checklist 14), and cognitive symptoms (Checklist for Cognitive and Emotional Consequences). Data analysis employed Spearman correlation and hierarchical multiple regression analyses.Results: A total of 265 patients (61% female; mean age of 51.7±13.7 years) were included in the study, with an average of 7.6±4.5 months following SARS-CoV-2 infection. Among them, 104 patients (40%) reported high levels of anxiety, 111 patients (43%) showed high levels depressive symptoms, and 71 patients (31%) demonstrated high levels of PTSS. Additionally, 200 patients (79%) reported experiencing more than 2 cognitive symptoms. Bivariate analyses indicated associations between psychiatric history and increased cognitive and psychological symptoms. Multivariate analyses revealed positive associations between physical symptoms and cognitive and psychological symptoms, and catastrophizing thoughts were associated with higher anxiety levels (β=.217, p<.001). Conversely, positive refocusing was associated with lower depressive symptoms (β=-.325, p<.001), PTSS (β=-.290, p<.001), and cognitive symptoms (β=-.220, p<.001).Discussion: Among non-hospitalized COVID-19 patients seeking care for persistent symptoms, approximately one-third reported high levels of psychological symptoms, and more than threequarter experienced cognitive symptoms. Physical symptoms, psychiatric history, and a tendency to catastrophize were identified as potential risk factors for persistent psychological and cognitive symptoms. Conversely, positive refocusing demonstrated a protective effect. These findings contribute to the understanding of long-term COVID-19 outcomes and emphasize the importance of integrating a biopsychosocial perspective into treatment approaches.